Investigating the relationship between metacognitive and critical thinking skills in preservice teachers: Insights from predict-observe-explain and direct instruction learning models - Shefa Dwijayanti Ramadani; Bea Hana Siswati; Serafica Btari Christiyani Kusumaningrum (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2025)
Metacognitive and critical thinking skills are widely recognized as essential components of higher-order thinking and play a key role in supporting academic success and lifelong learning. However, research exploring the interplay between these skills has often been conducted partially. This study aims to: (1) investigate the relationship between metacognitive and critical thinking skills within the active learning strategy Predict-Observe-Explain (POE) and direct instruction learning models (DI); and (2) analyze differences in the metacognitive and critical thinking skills scores of students taught with POE and DI learning strategies. A quantitative research method with a correlational design was used in this study. Data were collected from essay tests integrated with metacognitive and critical thinking skills rubrics at the end of the implementation of learning in classes that apply POE and DI. The data obtained were then analyzed using regression and t-tests. The results indicate a positive, strong, and significant relationship between metacognitive skills and critical thinking in both learning models. Additionally, the average critical thinking scores were significantly higher in the POE model than in DI, while there was no significant difference in students’ metacognitive skills. These findings suggest that constructivist-based POE learning can effectively promote critical thinking. Consequently, educators are encouraged to incorporate POE into instructional practices to support the development of metacognitive and thinking skills among students.Abstrak. Keterampilan metakognitif dan berpikir kritis telah dikenal luas sebagai komponen penting dari kemampuan berpikir tingkat tinggi, serta memiliki peranan kunci untuk mendukung keberhasilan akademis maupun kemampuan belajar sepanjang hayat. Akan tetapi, penelitian yang mengeksplorasi interaksi antara keterampilan ini sering kali dilakukan secara parsial. Penelitian bertujuan untuk mengkaji hubungan antara keterampilan metakognitif dan berpikir kritis pada strategi pembelajaran aktif Predict-Observe-Explain (POE) dan pembelajaran langsung (DI), serta membandingkan efektivitas kedua strategi pembelajaran dalam menumbuhkan keterampilan tersebut. Metode penelitian eksperimental dengan desain korelasional digunakan dalam penelitian ini. Data dikumpulkan dari tes esai yang diintegrasikan dengan rubrik keterampilan metakognitif dan berpikir kritis pada akhir pelaksanaan pembelajaran di kelas yang menerapkan POE dan pembelajaran langsung. Data yang diperoleh kemudian dianalisis menggunakan regresi dan uji-t. Hasil penelitian menunjukkan bahwa terdapat hubungan yang positif, kuat, dan signifikan antara keterampilan metakognitif dan berpikir kritis pada implementasi kedua model pembelajaran. Adapun rerata skor keterampilan berpikir kritis secara signifikan lebih tinggi pada pembelajaran yang menerapkan POE dibandingkan model pembelajaran langsung, sementara keterampilan metakognitif mahasiswa tidak berbeda signifikan. Temuan ini menunjukkan bahwa strategi POE yang berbasis konstruktivisme dapat secara efektif meningkatkan pemikiran kritis. Oleh karenanya, pendidik diharapkan untuk mengintegrasikan POE ke dalam praktik pengajaran untuk mendukung pengembangan keterampilan metakognitif dan berpikir kritis siswa.